APPLICATION OF THE EKARINI EDUCATION MODEL IN PREVENTING DENTAL CARIES IN EARLY CHILDHOOD (INTERNATIONAL SEMINAR, 2025)
Background: Dental caries is still a major health problem in Indonesia, especially among children. Data shows that the prevalence of dental caries in Indonesia reaches 56.9% in children aged >3 years, which will have an impact on children's health and quality of life. Purpose: To determine the effect of the ‘Ekarini’ education model on improving children's knowledge and skills in brushing their teeth to maintain early childhood dental health through a structured educational approach based on children's developmental needs. Methods: This study used an experimental design with a one-group pretest-posttest approach. The population in this study were children aged 3–6 years at the Quran Hadits Kindergarten in Jambi City. The sample was selected using purposive sampling, resulting in a sample size of 140 children. Finding: The results of this study showed a p-value of 0.000